General Practitioners' Experiences During the First Phase of the COVID-19 Pandemic in Italy: A Critical Incident Technique Study - Kurotschka, Peter Konstantin; Serafini, Alice; Demontis, Michela; Serafini, Arianna; Mereu, Alessandro; Moro, Maria Francesca; Carta, Mauro Giovanni; Ghirotto, Luca (Frontiers in Public Health, 2021)
Since February 2020, when coronavirus disease began to spread in Italy, general practitioners (GPs) were called to manage a growing number of health situations. The challenges experienced by Italian GPs remained unrevealed. This study aimed at exploring Italian GPs' care experiences and practices associated with critical incidents during the first wave of the pandemic. A qualitative study design involving the critical incident technique through an online survey was applied. Sociodemographic data and open-ended responses were collected. While participants' characteristics were analyzed through descriptive statistics, qualitative data were thematically analyzed employing the framework method. 149 GPs responded to the survey and 99 participants completed the survey (dropout rate = 33%). Eight themes emerged indicating factors related to the organization of the healthcare system and factors related to the clinical management of patients, that were perceived as impacting on the GPs' care provision. The analysis revealed difficulties in communicating with other local services. This, together with the lack of coordination among services, was reported as a major challenge. Primary care was perceived as having been undervalued and criticalities in the organization of GP courses, led in a bureaucratic fashion, posed at risk some trainees to be infected. The digital technologies adopted for remote patient consultations were seen as useful tools for daily practice helping the GPs to stay emotionally connected with their patients. Besides, the improvement in the GP–patient relationship in terms of solidarity between patients and doctors and compliance to rules, had a positive impact. Moreover, many respondents addressed the importance of professional collaboration and teamwork, in terms of both support in practical issues (to find PPE, diagnostics and guidelines) and emotional support. At the same time, the lack of resources (e.g., PPE, swabs) and of specific guidelines and protocols impacted on the care provision. Our findings suggest that GPs in Italy are at risk of being left behind within the epidemic management. Communication and coordination among services are essential and should be substantially improved, and primary care research should be initiated to collect the context-specific evidence necessary to enhance the system's preparedness to public health emergencies and the quality of primary care services.